The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jpm11030235
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Biomarkers for Dental Caries Detection and Personalized Monitoring

Abstract: This study investigated the potential of salivary bacterial and protein markers for evaluating the disease status in healthy individuals or patients with gingivitis or caries. Saliva samples from caries- and gingivitis-free individuals (n = 18), patients with gingivitis (n = 17), or patients with deep caries lesions (n = 38) were collected and analyzed for 44 candidate biomarkers (cytokines, chemokines, growth factors, matrix metalloproteinases, a metallopeptidase inhibitor, proteolytic enzymes, and selected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 66 publications
(84 reference statements)
0
35
0
1
Order By: Relevance
“…The prevalence and damage generated by these bacteria are influenced by host protective factors, such as immune competence, the production and buffering capacity of saliva, and hygiene and dietary habits [ 5 ]. Mechanisms have been sought to diagnose the risk of caries based on these factors using software such as Cariogram [ 6 ] or through the identification of biomarkers [ 7 , 8 , 9 ]. However, a significant amount of new studies are required to evaluate the validity of caries biomarkers, among other things because tooth decay is a multi-factorial disease with genetic, environmental and microbial effects playing a role, and because of a large inter-individual variability that renders the task of finding universal caries markers [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence and damage generated by these bacteria are influenced by host protective factors, such as immune competence, the production and buffering capacity of saliva, and hygiene and dietary habits [ 5 ]. Mechanisms have been sought to diagnose the risk of caries based on these factors using software such as Cariogram [ 6 ] or through the identification of biomarkers [ 7 , 8 , 9 ]. However, a significant amount of new studies are required to evaluate the validity of caries biomarkers, among other things because tooth decay is a multi-factorial disease with genetic, environmental and microbial effects playing a role, and because of a large inter-individual variability that renders the task of finding universal caries markers [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…All the studies have also managed to produce positive correlation between the salivary protein biomarkers and dental caries. One study included in this review has found 4 reliable salivary markers out of existing potential 44 biomarkers and was discovered to have great promise as classifiers for distinguishing between healthy individuals and caries patients [5]. They were Interleukins IL-4 and IL-13, the interleukin receptor IL-2-RA and the chemokines eotaxin/CCL11 [5].…”
Section: Discussionmentioning
confidence: 99%
“…One study included in this review has found 4 reliable salivary markers out of existing potential 44 biomarkers and was discovered to have great promise as classifiers for distinguishing between healthy individuals and caries patients [5]. They were Interleukins IL-4 and IL-13, the interleukin receptor IL-2-RA and the chemokines eotaxin/CCL11 [5]. Another included study has found a positive correlation between IL-6 exhibitions with caries prediction [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paqué et al [15] investigated the potential of salivary bacterial and protein markers for evaluating the disease status in healthy individuals with caries. Saliva samples from caries and gingivitis-free individuals (n = 18), patients with deep caries lesions (n = 38) was collected and analysed for 44 candidate biomarkers namely: selected oral bacteria, growth factors, chemokines and proteolytic enzymes among others.…”
Section: Introductionmentioning
confidence: 99%